Charting Trends in Medicare Reimbursement for Lower Extremity Imaging. Issue 3 (18th March 2023) - LeBaron, Zachary G.; Richman, Evan H.; Brown, Parker J.; Minzer, Ian D.; Brinkman, Joseph C.; Hinckley, Nathaniel; Fox, Michael G.; Patel, Karan
Background: Medicare reimbursement is rapidly declining in many specialties. An in-depth analysis of Medicare reimbursement for routinely performed diagnostic imaging procedures in the United States is warranted. Purpose/Hypothesis: The purpose of this study was to evaluate Medicare reimbursement trends for the 20 most common lower extremity imaging procedures performed between 2005 and 2020, including radiographs, computed tomography (CT), and magnetic resonance imaging (MRI). We hypothesized that Medicare reimbursement for imaging procedures would decline substantially over the studied period. Study Design: Cohort study. Methods: The Physician Fee Schedule Look-up Tool from the Centers for Medicare and Medicaid Services was analyzed for reimbursement rates and relative value units associated with the top 20 most utilized Current Procedural Terminology (CPT) codes in lower extremity imaging from 2005 to 2020. Reimbursement rates were adjusted for inflation and listed in 2020 US dollars using the US Consumer Price Index. To compare year-to-year changes, the percentage change per year and compound annual growth rate were calculated. A 2-tailed t test was used to compare the unadjusted and adjusted percentage change over the 15-year period. Results: After adjusting for inflation, mean reimbursement for all procedures decreased by 32.41% ( P = .013). The mean adjusted percentage change per year was –2.82%, and the mean compound annual growth rate was –1.03%. Compensation for the professional and technical components for all CPT codes decreased by 33.02% and 85.78%, respectively. Mean compensation for the professional component decreased by 36.46% for radiography, 37.02% for CT, and 24.73% for MRI. Mean compensation for the technical component decreased by 7.76% for radiography, 127.66% for CT, and 207.88% for MRI. Mean total relative value units decreased by 38.7%. The commonly billed imaging procedure CPT 73720 (MRI lower extremity, other than joint, with and without contrast) had the greatest adjusted decrease of 69.89%. Conclusion: Medicare reimbursement for the most billed lower extremity imaging studies decreased by 32.41% between 2005 and 2020. The greatest decreases were noted in the technical component. Of the modalities, MRI had the largest decrease, followed by CT and then radiography.